(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
The movie trailer is a film genre whose purpose is to prompt the spectator to watch the promoted film. From the narrative point of view, it can be considered as an example of mini-fiction equivalent to the micro-story in narrative texts, due to its conciseness and brevity and its power of suggestion. The trailer summarizes the film, outlining the highlight moments of the film through various discoursive techniques, which will be featured in this article. We have chosen some Spanish movie trailers from different periods and genres to show that the trailer can be considered an autonomous genre.